The distribution and metabolism of hexabromocyclododecane isomers varies in the tissues of Nibea albiflora - Song, Suping; Sun, Xiumei; Cheng, Xin; Peng, Xijian; Hao, Qing; Hu, Hongmei; Zhu, Jian; Li, Tiejun; Guo, Yuanming (Frontiers in Environmental Science, 2023)
The present test investigated the selective accumulation, depuration, and bioisomerization of hexabromocyclododecanes (HBCDs) in different tissues and organs of Nibea albiflora, as well as the genetic metabolic behavior of HBCDs between parents and offspring. In a semi-static water environment, N. albiflora were exposed to individual HBCD diastereoisomers (α-HBCD, β-HBCD, or γ-HBCD) at a concentration of 0.4 μg/L for bioaccumulation, followed by clean food for depuration. During the exposure period, the highest concentrations of these HBCDs were observed in the intestine and gill of N. albiflora. α-HBCD was detected in all exposure groups, suggesting that both β-HBCD and γ-HBCD could be bioisomerized to α-HBCD in N. albiflora. In addition, there was no bioisomerization of α-HBCD to either β-HBCD or γ-HBCD, and there was no bioisomerization between β-HBCD and γ-HBCD. The half-lives (t1/2) were variable among different diastereoisomers, following an order of α-HBCD > γ-HBCD > β-HBCD. The most rapid depuration rate of HBCD was discovered th liver while muscle showed the least. Additionally, prior to spawning, the parent fish were exposed to contaminated feed (silkworms sprayed with 200 μL of a 30 μg/mL HBCD solution) for 6 days. By comparing the HBCDs concentrations in the maternal gonad, fertilized eggs, hatching eggs, larvae, and juveniles, it was determined that the maternal transfer coefficients for HBCDs were approximately 1, indicating dynamic equilibrium of HBCDs throughout the process from maternal tissue to progeny development. Differences in HBCD pattern between organs at the experiment support a proposal of an organ-specific diastereomer accumulation.